Examining the transition processes in the Pearl River Delta polycentric mega-city region through the lens of corporate networks. (February 2017) - Zhao, Miaoxi; Derudder, Ben; Huang, Junhao
Abstract: This paper presents an analysis of the shifting spatial organization of the Pearl River Delta (PRD), a large-scale urbanized region bordering Hong Kong that includes major cities, such as Guangzhou and Shenzhen, alongside a range of other fast-developing cities and towns. Our methodology measures and compares the different networking components of the PRD's spatial organization and uses data on the geography of firms' networks as observed in the links between locations of headquarters and subsidiaries in 2001, 2008 and 2013. We examine whether there has been a shift towards integrated polycentricity in the unfolding spatial organization of this 'workshop of the world' through functional polycentricity and a typology of the geographies of these links. The results suggest complex interaction processes in the PRD in which network interactions significantly increased in 2001–08 and slightly declined in 2008–13 (with the exception of manufacturing links, which are increasingly managed from headquarters in Guannei, Shenzhen). We argue that the PRD is increasingly characterized by a functional polycentric and cross-regional interaction pattern for market-oriented sectors; although more regionalized, networks continue to dominate sectors that have higher proportions of state-owned enterprises. Highlights: To assess the unfolding integration and polycentricity of the Pearl River Delta, we analyse data on firm ownership linkages through a combination of functional polycentricity and a classification of the spatial dimensions of these linkages. Network interaction in the PRD significantly increased in 2001-08, and slightly declined in 2008-13. By 2013, most of the Pearl River Delta's sub-regions were integrated in a complex web of linkages, with the functional polycentricity becoming more obvious. In spite of a variety of geographical shifts in linkages, outdegree centrality (and therefore headquarter locations) remains confined to the central parts of the Pearl River Delta. Linkages in the Pearl River Delta increasingly straddle the borders of prefecture-level regions.